Forty Fourth Meeting of the National Development Council May 22 - 23, 1992 Summary Record - Planning Commission (Planning Commission, 1992)
The National Development Council held its forty- fourth meeting at Parliament House Annexe, New Delhi on 22nd and 23rd May 1992, under the Chairmanship of Shri P.V. Narasimha Rao, Prime Minister, and Chairman of the Council. The meeting considered the Eighth Five Year Plan (1992-97) document.
Government of India Planning Commission
Government of India Planning Commission